A Selective Employment of Electronic Effects of the Pentafluorosulfanyl Group Across Linear and Tripodal Push-Pull Chromophores - Fecková, Michaela; Klikar, Milan; Vourdaki, Chrisovalantou; Georgoulis, Ioannis; Pytela, Oldřich; Achelle, Sylvain; Růžičková, Zdeňka; Fakis, Mihalis; Beier, Petr; Bureš, Filip (Royal Society of Chemistry, 2025)
Twelve model amino-based linear D-π-A and tripodal D-(π-A)3 chromophores bearing electron-withdrawing SF5-group(s) at different peripheral positions were designed and prepared in a straightforward way. The influence of the position and the number of SF5-groups was studied with the aid of single crystal X-ray analysis, thermal and electrochemical measurements, (non)linear steady-state and time resolved spectroscopies, and DFT calculations. Significant property tuning can be achieved when modulating the number and position of the (peripheral) SF5-group(s), e.g. increase of the thermal robustness from 300 to 420 °C, the HOMO–LUMO gap is tuned through an exclusive manipulation of the LUMO, and the absorption/emission maxima can be red-shifted. The para-positioning allowing their hyperconjugation and the increasing number of the appended SF5-groups along with a polar environment support the intramolecular charge-transfer and open a non-radiative deexcitation channel, while the two-photon absorption cross-section is generally enhanced for the para-substituted octupolar chromophores. Thus, properly placing the SF5-group(s) along the  conjugated backbone allows a principal tuning of the push-pull chromophore fundamental function(s).
Keywords: pentafluorosulfanyl; push-pull chromophore; negative hyperconjugation; two-photon absorption; electrochemistry